2019
DOI: 10.1016/j.csbj.2019.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous and Foreign Nucleoid-Associated Proteins of Bacteria: Occurrence, Interactions and Effects on Mobile Genetic Elements and Host's Biology

Abstract: Mobile Genetic Elements (MGEs) are mosaics of functional gene modules of diverse evolutionary origin and are generally divergent from the hosts´ genetic background. Existing biases in base composition and codon usage of these elements` genes impose transcription and translation limitations that may affect the physical and regulatory integration of MGEs in new hosts. Stable appropriation of the foreign DNA depends on a number of host factors among which are the Nucleoid-Associated Proteins (NAPs). These small, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 187 publications
0
15
0
Order By: Relevance
“…The proper balance between chromosome compaction and the availability of chromosomal regions for the protein complexes involved in different cellular processes depends mainly on the DNA binding activity of NAPs (Krogh et al, 2018;Flores-Ríos et al, 2019). These small basic proteins can condense chromosomal DNA by bending, wrapping, and/or bridging relatively distant DNA strands (Luijsterburg et al, 2006;Dillon and Dorman, 2010).…”
Section: Nucleoid Dynamics Are Orchestrated By Napsmentioning
confidence: 99%
“…The proper balance between chromosome compaction and the availability of chromosomal regions for the protein complexes involved in different cellular processes depends mainly on the DNA binding activity of NAPs (Krogh et al, 2018;Flores-Ríos et al, 2019). These small basic proteins can condense chromosomal DNA by bending, wrapping, and/or bridging relatively distant DNA strands (Luijsterburg et al, 2006;Dillon and Dorman, 2010).…”
Section: Nucleoid Dynamics Are Orchestrated By Napsmentioning
confidence: 99%
“…The predicted interaction of NinH with DNA was initially evaluated in an electrophoretic mobility shift assay with short 5 0 -32 P-radiolabeled substrates ( Figure 3A). Purified NinH bound to a 60 bp dsDNA (DS 60 ; Supplementary Table S1) forming two complexes ( Figure 3A, lanes 1-3; Supplementary Figure S5), confirming that it is capable of forming a stable association with DNA. To quantify this binding affinity of NinH for dsDNA we utilized fluorescence anisotropy of a 3 0 -fluorescein-tagged 20 bp duplex (DS 20 ; Figure 3B), which yielded an estimated K D of 57 nM for a NinH dimer.…”
Section: Ninh Dna Bindingmentioning
confidence: 75%
“…Several examples of NAP-like functions have previously been found associated with extrachromosomal elements [60], including Bacillus subtilis phage f29 p6 [61] and homologs of H-NS present in phage EPV1 [62] and conjugative plasmids R446 [63] and pSf-R27 [64]. H-NS is primarily a repressor of gene expression [65] and selfish DNA elements carrying versions of the protein may be harnessed to down-regulate bacterial defense genes to promote their persistence [64].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to bear in mind that the function of the foreign DNA sequence may also have an impact on its ability to integrate. A number of plasmids and other genetic elements carry genes for NAP orthologs that may affect NAP equilibrium and nucleoid structure in a host cell [21,96]. The upcoming years will possibly shed some light into the mechanisms of how the interactions between endogenous and foreign NAPs could affect the evolvability of the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…NAPs bend, wrap or bridge DNA, having different affinities to DNA, and they have recently been shown to be involved in the higher-order chromosome organization as well [12]. It has been shown that changes in the activity of NAPs influence DNA replication and repair and transposition of mobile DNA elements [19][20][21]. In addition, gratuitous repair could also be stimulated by specific DNA structures or dynamics such as transcription [22].…”
Section: Introductionmentioning
confidence: 99%